Time to initiation of adjuvant chemotherapy in patients with rapidly proliferating early breast cancer. Issue 14 (September 2015) - Farolfi, Alberto; Scarpi, Emanuela; Rocca, Andrea; Mangia, Anita; Biglia, Nicoletta; Gianni, Lorenzo; Tienghi, Amelia; Valerio, Maria Rosaria; Gasparini, Giampietro; Amaducci, Laura; Faedi, Marina; Baldini, Editta; et al.
Abstract Aim To evaluate the optimal time interval from definitive surgery to commencing chemotherapy in early breast cancer (EBC). Patients and methods The relationship between time to initiation of adjuvant chemotherapy (TTC), calculated in weeks, and disease-free (DFS) or overall survival (OS), was assessed in 921 EBC patients with rapidly proliferating tumours (thymidine labelling index >3% or G3 or Ki67 >20%), randomised in a phase III clinical trial (NCT01031030) to receive chemotherapy with or without anthracyclines (epirubicin → cyclophosphamide, methotrexate and fluorouracil (CMF) versus CMF → epirubicin versus CMF). DFS, OS and 95% confidence intervals (95% confidence interval (CI)) were calculated by the Kaplan–Meier method. Multivariate Cox analysis was performed in relation with nodal involvement, oestrogen receptor and human epidermal growth factor receptor 2 (HER2) status, Ki67 value, type of adjuvant chemotherapy, menopausal status and tumour size. Results At a median follow-up of 105 months (range 2–188), a prolonged TTC resulted in a significant increase in the risk of relapse: hazard ratio (HR) 1.15 (95% CI 1.02–1.30, p = 0.019). Using a backward elimination procedure, TTC, tumour size and nodal involvement remained significantly associated with DFS. A time-dependent receiver-operating characteristic (ROC) curve analysis was subsequently utilised to evaluate the best cut-off for TTC, identifying 7 weeks as the best threshold for longer OS (p = 0.043): 8-year OS 88% (95% CI 85–90) for patients with a TTC <7 weeks and 78% (95% CI 68–87) for the other group. Conclusions Our results confirm that a shorter TTC may reduce relapses and possibly also improve clinical outcome in patients with highly proliferating EBC.